Kepastian Hukum Pembagian Harta Bersama Karena Perceraian Terkait Harta Bersama Yang Dikuasai Oleh Salah Satu Pihak - Widagdo, Sarastyo Dwi; Turhamun, M.Slamet; Yani, Ahmad (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
In divorce, of course, there are parties who decide to divorce. There is a difference in mention between those who file a divorce case from the husband's side, and those who file a divorce case from the wife's side. The person or legal subject who files a divorce case in court is referred to as the parties or parties to the case. In the case of divorce, if the person filing for divorce is the husband, then the husband is then referred to as the "Applicant", while the wife is referred to as the "Respondent". On the other hand, if the person filing the divorce case is from the wife's side, then the wife is referred to as the "Plaintiff", while the husband is referred to as the "Defendant". Sometimes, legal subjects who litigate in judicial institutions are generally referred to as justice seekers, or commonly referred to as litigants, or more shortly, parties.The formulation of the problem in this study is how to divide the common property controlled by one party and how is the legal certainty of the division of common property controlled by one party. The theories used in this study are the Theory of Legal Certainty according to Satjipto Raharjo and the Theory of Joint Property according to Yahya Harahap. The method used in this study is a type of normative juridical research, namely literature law research or secondary data with primary, secondary and tertiary legal sources. The research approach used is a legislative approach, a case approach, and a conceptual approach, with the technique of collecting legal materials carried out by identifying and inventorying positive legal rules, book literature, journals and other sources of legal materials. For legal material analysis techniques, it is carried out by systematic interpretation and grammatical interpretation. The results of the research concluded that there was a dispute over the way of distribution of common property because the joint property was controlled by one of the parties and legal certainty about the division of common property controlled by one of the parties based on article 37 of Law No. 1 of 1974 concerning Marriage.